Design Of Religious Tourism Area - Putri Ayu Dewi Sekardadu Tomb - Based on Disaster Mitigation - Hapsari, Oktavi Elok; Qurrotul A'yun (Journal of Architectural Research and Design Studies, 2024)
This project aims to strengthen the Putri Ayu Dewi Sekardadu tomb, a religious tourism site in Sidoarjo, Indonesia, against natural calamities, particularly flooding. The study extensively researches catastrophe mitigation and architectural enhancements for religious tourism. We evaluate flood risks, examine infrastructure, and provide design solutions to improve accessibility, amenities, attraction, and ancillary services using observational research and data analysis. The study recommends combining structural improvements with community-based techniques to mitigate disasters. The findings emphasize the importance of community engagement, disaster readiness, and sustainable design in developing resilience and improving cultural tourism. By analyzing and addressing these aspects, interested parties can promote a tourism experience that can withstand natural calamities and increase cultural value. Keywords: Dewi Sekardadu; Religion; Tomb; Sidoarjo; Tourism Area